2013
DOI: 10.4195/nse.2012.0027
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Water Attitudes, Perceptions, and Learning Preferences on Water-Conserving Actions

Abstract: Water conservation is an important natural resource issue, and the focus of a number of educational and extension programs. Inherent in many programs is the causal link between water facts and conservation behaviors that affect water quality and/or quantity. This article interprets the results of a survey on attitudes and perceptions of water resources (n = 2226) from nine states (Alabama, Arizona, Florida, Georgia, Hawaii, Mississippi, Oklahoma, Tennessee, and Texas). The goal of the survey was to assess atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…Weather, rates, income, household composition, housing characteristics, frequency of billing, and type of outdoor irrigation are major drivers of residential water demand [ Arbués, et al ., 2003; Duke et al ., ; Grafton et al ., ; Hewitt and Hanemann , , Olmstead et al ., ; Olmstead and Stavins , 2008; Ramachandran and Johnston , ; Shandas and Parandvash , ; Shearer , ; Wentz and Gober , ; Worthington and Hoffman , ]. Only recently, the analysis has taken into account consumers' behaviors and attitudes and new studies include consumers' believes as potential drivers of water consumption [ Adams et al ., ; Beal et al ., ; Cook et al ., ; March et al ., ].…”
Section: Water Conservation As Natural Resources and Water Demand Manmentioning
confidence: 99%
See 1 more Smart Citation
“…Weather, rates, income, household composition, housing characteristics, frequency of billing, and type of outdoor irrigation are major drivers of residential water demand [ Arbués, et al ., 2003; Duke et al ., ; Grafton et al ., ; Hewitt and Hanemann , , Olmstead et al ., ; Olmstead and Stavins , 2008; Ramachandran and Johnston , ; Shandas and Parandvash , ; Shearer , ; Wentz and Gober , ; Worthington and Hoffman , ]. Only recently, the analysis has taken into account consumers' behaviors and attitudes and new studies include consumers' believes as potential drivers of water consumption [ Adams et al ., ; Beal et al ., ; Cook et al ., ; March et al ., ].…”
Section: Water Conservation As Natural Resources and Water Demand Manmentioning
confidence: 99%
“…Summary studies find that price elasticity is higher for ascending block pricing [ Dalhuisen et al ., ; Olmstead et al ., ], but also that price elasticity is smaller in the winter [ Hanemann and Nauges , ], elasticities are lower for renters rather than for homeowners, and low income customers' demand has lower elasticity than high income's [ Duke et al ., ; Grafton et al ., ; Renwick and Archibald , ; Worthington and Hoffman , ]. Outdoor uses are more elastic than indoor [ Mansur and Olmstead , ], and for smaller properties price elasticity is lower than for larger properties [ Adams et al ., ].…”
Section: Water Conservation As Natural Resources and Water Demand Manmentioning
confidence: 99%
“…They found that both traditional (rural) and new (urban) audiences have high interest in water resource–related topics and that extension water resource programs reached 15% or more of the adult population in the Southern, Mid‐Atlantic, and Northeastern states. In turn, Adams et al (2013) evaluated the impact of knowledge‐based water conservation programs (including traditional education programs) vs. non‐knowledge‐based factors on peoples’ water conserving behaviors. The article shows that receiving water resource information from extension or environmental groups through active learning increases the likelihood of adopting outdoor water conservation, whereas passive learning such as from newspapers and TV is associated with lower outdoor water conservation.…”
Section: Resultsmentioning
confidence: 99%
“…The articles in this series also demonstrate the importance of water resource extension programs to be tailored to the specific audiences. Specifically, urban or rural characteristics of the community of residence (along with demographics) are shown to significantly correlate with the preferences for information delivery modes (Boellstorff et al, 2013), water resource topics of interest (Boellstorff et al, 2013), and the level of concerns about water quality (Borisova et al, 2013) and availability (Adams et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggested there was an opportunity to focus on individuals who assigned high importance to plentiful water but who were unengaged in conservation practices . In another study, Adams et al (2013) found people who perceived water quality, water conservation in residential landscapes, and water for other purposes as being important were more likely to engage in water conservation behaviors outside their homes. Other researchers found individuals responded more positively to assertive requests if the topic of the message was important to them (Kronrod, Grinstein, & Wathieu, 2012).…”
Section: Conceptual Frameworkmentioning
confidence: 98%